Disulfiram Inclusion Complexes - A Nebulization Approach to Fight COVID-19 - Ana Maria Pereira; Ayse Kaya; Dan Alves; Niusha Ansari-Fard; Mohammad Najlah (University of Huddersfield Press, 2022)
Disulfiram (DS) has an excellent anti-viral activity; however, its low water-solubility and first-pass metabolism are limiting its clinical applications. Cyclodextrins (CDs) have been used as solubility enhancers and carriers of DS proposed for inhalation to treat SARS-CoV-19. Two types of CDs (hydroxypropyl β-cyclodextrin and sulfobutyl ether β-cyclodextrin) were used to form inclusion complexes with DS, and drug solubility was assessed using spectrophotometric analytical method. Formulations were freeze-dried and characterized using DSC, TGA and FTIR. Nebulization technique was used to assess the potential for generating aerosols. All inclusion complexes are proved to be suitable for inhalation, therefore, potentially effective therapy for further investigation against SARS-CoV-19 is shown.